IMPLEMENTASI URBAN FARMING MELALUI TANAM BIBIT CABAI RAWIT DAN BAWANG MERAH DI KELURAHAN CIHAURGEULIS BANDUNG - Andhani, Aulia Zeta; Khoirunnisa Apriyani, Ria; Royani, Abdul (Jurnal Pengabdian Kepada Masyarakat, 2024)
Population density due to high mobility of rural residents to cities has an impact on land conversion, environmental quality degradation and limited food supply. Urban Farming is an effort to utilize limited land in urban areas for farming and livestock activities. The aim of this urban farming activity is to provide understanding, increase knowledge, and facilitate residents regarding the implementation of the urban farming concept through conventional planting of cayenne pepper and red onion seeds on limited land at RW 03 Cihaurgeulis Village in order to overcome the existing food inequality problem. In the city of Bandung by gardening to meet the food needs of his own family. The method used is descriptive qualitative which consists of socialization and practice of procedures and uses of urban farming. Keywords: Red Onion, Cayenne Pepper, Urban Farming.